Prognostic significance of survivin, β-catenin and p53 expression in urothelial carcinoma - Senol, Serkan (Bosn J Basic Med Sci, 2015)
Survivin, β-catenin, and p53 are well-known cell-cycle and apoptosis regulators. Urothelial carcinomas (UCs) are common, taking fourth place in men and ninth place in women. Compared to superficial tumors (Ta, CIS, or T1), invasive UCs are important with regard to recurrence, progression, and mortality. We tested the utility of the survivin, β-catenin, and p53 as biomarkers for early prediction of the invasiveness of UCs and the overall survival of the patients. We investigated high stage UC (n=147) and non-muscle invasive UC (NMI-UC) (n=113), using tissue microarray and immunohistochemistry. Spearman’s correlation and multivariate Cox regression were used for statistical processing of the data. High expressions of β-catenin, survivin, and p53 were associated with high T stage, recurrence, progression, mortality, low recurrence-free survival, low progression-free survival and low overall survival (p < 0.01). Similar findings were achieved for recurrence and progression in the NMI-UC group, except for mortality. Moreover, a positive correlation was shown between p53 and β-catenin and between p53 and survivin (r=0.221, p < 0.01; r=0.236, p < 0.01, respectively). Survivin, p53, and β-catenin overexpression may have prognostic significance, indicating the aggressive behavior and poor prognosis of UCs. Dysregulation of those these cell-cycle and apoptosis regulators in bladder carcinoma could be used as a molecular marker to determine the best treatment strategy and could contribute to the development of targeted therapies.